The temptation motif in the short prose of N.V. Gogol (Eurasian Journal of Philology Science and Education, 2015)
One of the major themes in Gogol’s works is the penetration of infernal forces into human life. Unlike his first cycles of stories («Evenings on a Farm Near Dikanka», «Mirgorod») with its rather pagan way ofconceiving this theme (tribal curse, spells, folk-beliefs), his next cycle, «Petersburg Tales», can already be characterized by the correlation with the Christian system of values. One of the key motifs of the cycle isthe temptation motif. With few exceptions, characters yield to temptation and choose the way of sin. In most cases the author’s positive ideal remains «offscreen»; it is only implied and not realized. The veryessence of Gogol’s tragic world perception is in this impossibility to incarnate the positive concept.
Keywords: temptation motif; Gogol’s stories; pagan world view; Christian system of values; positive ideal